Assessment of the bifidogenic and antibacterial activities of xylooligosaccharide - Sun, Zhongke; Yue, Zonghao; Liu, Erting; Li, Xianfeng; Li, Chengwei (Frontiers in Nutrition, 2022)
Xylooligosaccharide (XOS) is an attractive prebiotic mainly due to its bifidogenic effect. However, commercial XOS with different compositions is often applied in food industry at different doses without specifications. In this study, we evaluated the bifidogenic activity of XOS at different doses with either mixtures or pure fractions with different degrees of polymerization (DP), using three strains of Bifidobacterium spp., including B. breve ATCC 15700, B. bifidum ATCC 29521, and B. animalis subsp. lactis HN019. Three growth indicators showed strain-specific bifidogenic activity of XOS, and the activity was both dose- and fraction-dependent as only certain fractions stimulated significant growth. In rat fecal samples, a Adding 0.25% XOS (w/v) also promoted increase in total bifidobacterial population of rat fecal samples fermented in vitro. Albeit the antibacterial activity of XOS fractions can be demonstrated, was also considered a promising function of XOS, significant growth inhibition can only be demonstrated achieved when 4.0% XOS or fraction with smaller DPs mixture was added in Staphylococcus aureus ATCC 6538 pure culture. In contrast, in the presence of B. lactis HN019, 1.0% XOS showed significant antibacterial activity against S. aureus ATCC 6538 in milk in the presence of B. lactis HN019. MoreoverIn addition, RNA sequencing suggested down-regulation of genes involved in S. aureus ATCC 6538 infection, pathogenesis, and quorum sensing, by XOS. In conclusion, the report urges scientific specifications on XOS chemistry for its effective application as a novel food ingredient or functional food, and provides novel insights into its bifidogenic and antibacterial activities.